Soil quality restoration and yield stabilization in acidic soils of northeastern Himalayas: Five years impact of green manuring and crop residue management - Ansari, Meraj A.; Babu, Subhash; Choudhary, Jairam; Ravisankar, Natesan; Panwar, Azad S. (Frontiers in Environmental Science, 2022)
Soil quality restoration and crop productivity maximization is the global challenge to feed the galloping population. The task is much more daunting in a risk prone, fragile and low productive hilly region due to depletion of supporting and regulatory ecosystem services. Five-year long-term (2012-2017) field experiment was conducted to stabilize the yield and soil quality through legume green manuring and crop residue recycling in maize-based cropping systems in the eastern Himalyan region of India. Four green manures [green gram (Vigna radiata); cowpea (Vigna unguiculata); sesbania (Sesbania aculeata) along with control (no-green manure)], three cropping systems [groundnut (Arachis hypogaea) –pea (Pisum sativum); maize (Zea mays) –pea, and maize + groundnut –pea] and two levels of residue management practices [residue removal and residue retention] were evaluated in split-plot design with three replications. Among the green manure options, Sesbania had a significant effect on soil organic carbon (SOC) stock, soil micro (Fe, Mn, Zn, and Cu), and macronutrients (N, P and K) on the surface (0-0.15 m) and subsurface (0.15-0.45 m) soil. The improvement in soil enzymatic activities (acid phosphatase, alkaline phosphatase, dehydrogenase, beta-glucosidase, and aryl sulphatase activity) (p<0.05) in Sesbania treated soil was +28.1 to +38.9% in surface and +18.3 to +27.3% in subsurface soil over non-green manure plot. Sesbania-treated soils also exhibited higher soil quality index (SQI) and stratification (SR) of nutrients and soil enzymes than non-green manure soils. Among the cropping systems, groundnut intercropped with maize followed by peas with retention of their residues increased (p< 0.05) soil macro and micronutrients, SOC stock, soil enzymes, SR, and SQI than the other cropping systems. Sesbania green manuring and residues retention improved the yield sustainability by +19 and +11% in maize + groundnut-pea (MGP) cropping systems over non-green manuring and residue removal, respectively. Therefore, the incorporation of Sesbania as green manuring in MGP cropping systems with residue retention is recommended for stabilizing the soil quality through enhancing supportive and regulatory ecosystem services along with maintaining long-term sustainable productivity in the Indian Himalayan region.